Algebra 1: Common Core (15th Edition)

Published by Prentice Hall
ISBN 10: 0133281140
ISBN 13: 978-0-13328-114-9

Chapter 6 - Systems of Equations and Inequalities - 6-2 Solving Systems Using Substitution - Practice and Problem-Solving Exercises - Page 375: 17


(-11, -19)

Work Step by Step

We first add 2x to both sides of the first equation to obtain that y=2x+3. Thus, in the second equation, wherever we see y, we will substitute 2x+3, and then we will solve: $3x -2(2x+3) = 5 \\\\ -x-6=5 \\\\ -x =11 \\\\ x=-11$ We now substitute x=-11 back in: $y=2(-11)+3=-19$ We plug this point back into the first equation and find that our answer is correct.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.